Fire sword and sea : a novel - Riley, Vanessa (William Morrow, 2026)
"From Vanessa Riley, acclaimed author of Queen of Exiles, comes a dual-timeline saga based on the life of the legendary pirate Jacquotte Delehaye, a fearless woman of mixed parentage who forged her own life plundering wealth and battling slavers on the treacherous Caribbean seas of the 17th century"--